Asuhan Kebidanan Postpartum pada Ny. M P2A0 di TPMB Hj. Siti Saidah, S.Keb., Bdn Kota Banjarmasin - Jahratul Muna; Merlin Karinda; Syahrida Wahyu Utami (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
According to the World Health Organization (WHO), in 2023 more than 700 women died every day from preventable causes related to pregnancy and childbirth, with 92% of these deaths occurring in low- and middle-income countries, including Indonesia. In South Kalimantan, the maternal mortality rate (MMR) in 2023 reached 145 per 100,000 live births, an increase from 136 in 2022, with the main causes being hemorrhage and hypertensive complications. This study aims to provide postpartum midwifery care for Mrs. M, P2A0, from the first postpartum visit (KF1) to the fourth (KF4) at TPMB Hj. Siti Saidah, S.Keb., Bdn, in Banjarmasin City. The method used is descriptive with a case study approach using the SOAP format. The care was conducted from May 14 to June 26, 2025, at the TPMB and the client’s home. Data were collected through interviews, observations, medical records, physical examinations, supporting tests, and documents from related institutions. The results showed that the client was in good general condition, conscious (compos mentis), with blood pressure of 110/90 mmHg, respiratory rate of 22 breaths/minute, pulse rate of 82 beats/minute, temperature of 37°C, good uterine contractions, lochia rubra, and a first-degree perineal tear. The care provided was in accordance with midwifery standards, proceeded smoothly, and revealed no discrepancies between theory and practice.